Deep tilling and localized liming improve soil chemical fertility and sugarcane yield in clayey soils - de Campos, Murilo [UNESP]; Rossato, Otávio Bagiotto; Marasca, Indiamara; Martello, Jorge Martinelli [UNESP]; de Siqueira, Gabriela Ferraz [UNESP]; Garcia, Ciro Pozzi; Rossetto, Raffaella; Calonego, Juliano Carlos [UNESP]; Cantarella, Heitor; Crusciol, Carlos Alexandre Costa [UNESP] (Elsevier, 2022)
The selection of an appropriate soil tillage system for improving yields and longevity is an important decision in sugarcane cultivation. In the present study, the effects of different soil tillage systems and methods of applying lime on sugarcane stalk and sugar yield performance as well as soil fertility parameters were evaluated throughout the sugarcane crop cycle. The experiments were established in two locations in April 2015 and conducted until August 2019, corresponding to a total of 4 growing seasons. A field study with a randomized block design was established with four replicates considering 4 treatments: conventional soil tillage system (CT), deep strip-tillage system (DT) and modified deep strip-tillage system (MDT), all with the same lime rate; and a standard treatment (control, CT without liming). Immediately after harvesting plant cane (18 months (mo) after planting), first ratoon (30 mo after planting), second ratoon (42 mo after planting) and third ratoon (54 mo after planting), soil samples were collected from a depth of 0.0–1.00 m, stratified every 0.2 m. Leaf material was sampled during the period of full vegetative growth. Analyses of soil chemical fertility, leaf concentrations of elements, and sugarcane yield components were performed. MDT was found to correct soil acidity most efficiently, mainly due to the positioning of the lime application. Under high aluminum saturation (AS), especially in deeper layers, deep lime placement was more effective and resulted in the best distributions of calcium (Ca2+) and magnesium (Mg2+), the highest base saturation (BS) and the lowest AS compared with the other treatments. Lime application was more important than the tillage system for improving the sucrose concertation and total recoverable sugar (TRS), whereas the tillage system affected the stalk yield and, consequently, the yield of sugar. Compared with DT and CT, the average stalk yield was 4.1% and 9.4% higher, respectively, under MDT at Macatuba and 6.3% and 15.3%, higher, respectively, under MDT at Piraju. Similarly, MDT improved average sugar yield by 3.7% and 10.4% at Macatuba and 6.1% and 16.3% at Piraju. Overall, long-term assessments, which are important for semi-perennial crops like sugarcane, showed that the both deep strip-tillage were most effective.
Keywords: Aluminum saturation; Base saturation; Conventional soil tillage; Deep strip-tillage; Lime application in bands